Philosophy Conception and Juridical Norm in The Theory of Islamic Macroeconomics - Hakim, Cipta Lukmanul (ITB AAS INDONESIA Surakarta, 2024)
Islamic economics is a relatively new discipline, even though its practice has been carried out along with the birth of Islam itself. Many people doubt the existence of Islamic economics, because so far in the general public there are only two mainstream economic systems known, namely capitalism and socialism. In addition, in Islamic society itself, Islamic economics is identified with muamalat fiqh. Muamalat fiqh in Islamic economics is placed in a very important position, because muamalat fiqh is the basis of theories in Islamic economics. The purpose of this research is to find out the philosophical review and juridical norms originating from the Al-Qur'an and al-Hadith regarding macro theory according to the perspective of Islamic law. The methodology of this article uses a literature study with descriptive analysis. Data were obtained from various books, research journals and online sources. The results of the research show that the instructions from the Qur'an and al-Hadith are not specifically divided into two groups, namely the macro and micro levels. However, the existence of juridical norms exists at every level of the Islamic economic system.